Autophagy and proteasomes in thymic epithelial cells: essential bulk protein degradation systems for immune homeostasis maintenance - Yamaguchi, Noritaka; Takakura, Yuki; Akiyama, Taishin (Frontiers in Immunology, 2024)
The thymus is a central organ that controls T cell development. Thymic epithelial cells (TECs) create a unique microenvironment essential for the differentiation of major histocompatibility complex (MHC)-restricted and self-tolerant T cells. TECs present a complex of self-peptides and MHC molecules (self-pMHCs) to immature T cells and regulate their survival and differentiation based on their affinity for self-pMHCs. The processing of self-peptides in TECs depends on bulk protein degradation systems, specifically autophagy and proteasomes. Studies using autophagy-and proteasome-deficient mouse models have demonstrated that these degradation systems in TECs are indispensable for maintaining immune homeostasis. Although autophagy and proteasomes are ubiquitous in nearly all eukaryotic cells, TECs exhibit unique characteristics in their autophagy and proteasome functions. Autophagy in TECs is constitutively active and independent of stress responses, while TEC proteasomes contain specialized catalytic subunits. This review summarizes the distinctive characteristics of autophagy and proteasomes in TECs and their roles in immune system regulation.